Crystallization and initial X-ray diffraction analysis of a mannose-binding lectin from champedak - Gabrielsen, M.; Abdul-Rahman, P.S.; Isaacs, N.W.; Hashim, Onn Haji; Cogdell, R.J. (2010)
Mannose-binding lectin from champedak (Artocarpus integer) is a homotetramer with a single-monomer molecular weight of 16 800 Da. Previous work has shown it to bind IgE and IgM, as well as being a mitogen of T cells in humans. Champedak mannose-binding lectin has successfully been used to detect altered glycosylation states of serum proteins. The protein was crystallized at 293 K in space group P2(1)2(1)2(1) (unit-cell parameters a = 76.89, b = 86.22, c = 95.37 angstrom) and the crystals diffracted to 2.0 angstrom resolution.